Gendered Perceptions of Interethnic Romantic Leads: A Case Study of Sepet and Mukhsin - Aida Maisarah Razak (Art and Society, 2025)
This paper explores how interethnic romance is gendered in Malaysian cinema through a comparative analysis of Yasmin Ahmad’s Sepet and Mukhsin. In a society where Malay-Muslim femininity is both culturally idealized and institutionally regulated, the representation of a Malay female protagonist engaging in romantic or affective bonds with a non-Malay counterpart carries complex cultural weight. Through close textual analysis, audience perception data, and aesthetic examination, the study illustrates how Yasmin Ahmad navigates national taboos around race, religion, and gender not through overt challenge, but through what this paper terms “soft transgression”—emotional nuance, narrative restraint, and cinematic empathy. Using a gender-aware lens, the paper highlights how female emotional agency, male vulnerability, and childhood intimacy are deployed to unsettle normative scripts of racial purity and heteropatriarchal authority. Viewer identification patterns across ethnic and gender lines reveal that affective resonance often transcends cultural boundaries, while also exposing generational discomfort with femininity in expressive roles. By situating these films within broader Southeast Asian cinematic and sociopolitical contexts, the paper argues for a framework of reading interethnic romance that is intersectional, emotionally attuned, and sensitive to the symbolic politics of gendered visibility.